ANALYSIS OF THE EXPENDITURE REALIZATION OF THE PERSONNEL BUREAU OF THE SECRETARIAT GENERAL OF THE MINISTRY OF HOME AFFAIRS - Rozan Fitra Hanandi (Journal Accounting International Mount Hope, 2026)
A budget is an estimate prepared to estimate expenditure for a certain period of time with the aim of estimating the amount of costs needed to finance all planned programs and activities that can be available and implemented optimally. The aim of this scientific study is to determine the level of effectiveness of budget absorption by the Civil Service Bureau of the Secretariat General of the Ministry of Home Affairs for the period 2020 - 2022. Descriptive analysis and data analysis are the methods used in this research using a calculation method for measuring the level of effectiveness of budget absorption. The results of this research show that the level of effectiveness in absorbing the budget for the Personnel Bureau of the Secretariat General of the Ministry of Home Affairs for the period 2020 - 2022 is classified as effective for the three periods of the fiscal year. The high level of effectiveness of budget realization that has been achieved indicates good and optimal budget implementation. Efforts will continue to be made to increase the effectiveness of budget absorption by increasing coordination and collaboration between relevant parties with an interest in the budget in the implementation of budget realization..